1995
DOI: 10.1192/pb.19.1.4
|View full text |Cite
|
Sign up to set email alerts
|

The experience of patient suicide among Irish psychiatrists

Abstract: One hundred and nine consultant psychiatrists completed an anonymous questionnaire on the suicide of patients in their care. A patient suicide was reported by 82%, of whom 47% had experienced their first patient suicide within five years of entering psychiatric practice. A formal review of the suicide had occurred In 24% of cases. The study examines the perceived effects of their first patient suicide on the professional practice of the respondents, and measures the personal stress related to It, using the Imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
3
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 7 publications
5
36
3
3
Order By: Relevance
“…Parmi les proches affectés se trouvent les professionnels de la santé qui la traitaient avant qu'elle ne meure. La recherche indique que le suicide d'un patient est un événement fréquent dans la pratique clinique des professionnels en santé mentale : 22 % à 39 % des psychologues (Chemtob et al, 1989 ;Trimble et al, 2000) et 51 % à 82 % des psychiatres (Chemtob et al, 1989 ;Cryan et al, 1995) ont rapporté avoir vécu cet événement dans l'exercice de leur profession. Aucune donnée empirique n'existe en ce qui concerne le nombre d'infirmiers(ères) en psychiatrie affectés (Collins, 2003).…”
Section: Résuméunclassified
“…Parmi les proches affectés se trouvent les professionnels de la santé qui la traitaient avant qu'elle ne meure. La recherche indique que le suicide d'un patient est un événement fréquent dans la pratique clinique des professionnels en santé mentale : 22 % à 39 % des psychologues (Chemtob et al, 1989 ;Trimble et al, 2000) et 51 % à 82 % des psychiatres (Chemtob et al, 1989 ;Cryan et al, 1995) ont rapporté avoir vécu cet événement dans l'exercice de leur profession. Aucune donnée empirique n'existe en ce qui concerne le nombre d'infirmiers(ères) en psychiatrie affectés (Collins, 2003).…”
Section: Résuméunclassified
“…The principle of equivalence of care states that prisoners are entitled to the same standard of healthcare as they would have were they not in prison. [2][3][4] Those prisoners who have mental disorders of a nature or degree such that their needs can only be appropriately met by in-patient treatment are meant to be transferred from prison to hospital for treatment. 5 Prison in-reach teams take referrals from a wide range of sources and generally support a high volume of prisoners with stable mental illnesses.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…2 Despite it potentially being one of the most distressing events in a psychiatrist's career, the number of studies in the literature is relatively small and there has been only one Irish study to date. 3 The studies conducted thus far have all identified patient suicide as a cause of considerable distress, yet it is an event for which training leaves psychiatrists underprepared. We conducted a nationwide study of all consultant adult psychiatrists in Ireland to establish the impact on their personal and professional life.…”
mentioning
confidence: 99%
“…Many psychiatric residents were included in this experience along with innumerable staff of other disciplines. The impact of any given suicide on staff varies, but the overall distress engendered may be substantive (44)(45)(46)(47)(48)(49). It is hypothesized that the distribution of suicide cases among attending physicians reflects both the length oftheir hospital appointment and their degree of exposure to high-risk case loads (that is, inpatients, those with schizophrenia, and those with severe affective disorders).…”
Section: Methodsmentioning
confidence: 99%